2014
DOI: 10.1016/j.scitotenv.2014.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Red mud a byproduct of aluminum production contains soluble vanadium that causes genotoxic and cytotoxic effects in higher plants

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…Whilst there have been no published studies on application of residue leachates to soils and substrates, Lehoux et al 2013 2013). Soluble V in the pH 11.1 treatment was a magnitude of 10 times lower than values reported likely to cause genotoxic effects in plants (Mišík et al 2014). Although leachate additions in the current study raised substrate pH levels, all values were considerably lower than pH 9.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Whilst there have been no published studies on application of residue leachates to soils and substrates, Lehoux et al 2013 2013). Soluble V in the pH 11.1 treatment was a magnitude of 10 times lower than values reported likely to cause genotoxic effects in plants (Mišík et al 2014). Although leachate additions in the current study raised substrate pH levels, all values were considerably lower than pH 9.…”
Section: Discussioncontrasting
confidence: 65%
“…Although leachate additions in the current study raised substrate pH levels, all values were considerably lower than pH 9. Mišík et al (2014) suggested that pH control of soil to pH 9 in residue affected soils would mitigate high aqueous concentrations phytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analyses has shown that it also contains radionuclides (e.g. 40 K, 226 Ra, and 230 Th), as well as, heavy metals such as Cd, Co, Cr, Ni and V [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no CSBTS and SQG levels for V, it is present at concentrations well above the Dutch intervention standards. This is of particular concern due to the noted mobility of V in waters in contact with red mud (Burke et al, 2012Lehoux et al, 2013;Mišík et al, 2014).…”
Section: Comparison Of Total Heavy Metals In Rm and Relevant Environmmentioning
confidence: 99%